2016
DOI: 10.1056/nejmoa1509117
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Labor Induction in Women 35 Years of Age or Older

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.ukThe new england journal of medicine n engl j med 374;9 nejm.org

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(89 citation statements)
references
References 27 publications
8
75
3
3
Order By: Relevance
“…2527 Increasing rates of maternal complications and arrest of labor, whether spontaneous or induced, are also seen with prolonged gestations. 20,28 While evidence suggests that induction of labor does not increase risk of cesarean delivery in the general population, 20,29 multiple studies have shown that obesity is a risk factor for failed induction. 16 Obese women have increased morbidity with cesarean deliveries, most notably wound complications, making this population even more susceptible to the morbidity associated with increased cesarean rates.…”
Section: Resultsmentioning
confidence: 99%
“…2527 Increasing rates of maternal complications and arrest of labor, whether spontaneous or induced, are also seen with prolonged gestations. 20,28 While evidence suggests that induction of labor does not increase risk of cesarean delivery in the general population, 20,29 multiple studies have shown that obesity is a risk factor for failed induction. 16 Obese women have increased morbidity with cesarean deliveries, most notably wound complications, making this population even more susceptible to the morbidity associated with increased cesarean rates.…”
Section: Resultsmentioning
confidence: 99%
“…Primarily, risk of eCS following failed IOL in nulliparous AMA women has never been revealed. Although previous studies have shown that maternal age is a considerable factor related to labor management, 6,12 a recent randomized controlled trial by Walker et al 18 showed conflicting results. In their study, women were randomly assigned to IOL or expectant management between 36 + 0 days and 39 + 6 days of gestation.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism responsible for the increased risk of intrauterine fetal death without structural defects in older women has not been explained so far. A meta-analysis of randomized trials has shown that induction of labor in women over 35 years of age is not associated with an increased risk of maternal or fetal complications and caesarean section [49,50]. Due to the risk of stillbirth in pregnant women of advanced reproductive age, it is recommended to treat pregnancies of women aged 40 and more as biologically mature at 39 weeks and consider the possibility of labor induction.…”
Section: Labor Induction In Pregnant Women Of Advanced Reproductive Agementioning
confidence: 99%